THE INFLUENCE OF BRAND POSITIONING FUN, ART AND EDUCATION BALE SENI BARLI-KOTA BARU PARAHYANGAN TOWARD VISIT DECISION IN BALE SENI BARLI-KOTA BARU PARAHYANGAN - Octaviany, Vany; Shiddiq, Muhammad Asyari (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
Bale Seni Barli-Kota Baru Parahyangan is one tourist attraction (DTW) art which is located in Kota Baru Parahyangan, Padalarang. Number of tourists visiting Bale Seni Barli-Kota Baru Parahyangan from year to year has increased, but did not meet the expected targets visit the manager. Building a strong Brand Positioning able to provide a reference for tourists in choosing DTW to be addressed which can then influence the decision of tourists to visit a DTW. Therefore Bale Seni Barli-Kota Baru Parahyangan trying to build a strategy Brand Positioning Fun, Art and Education in order to position itself as DTW which offers attractions and tourist activity-laden art education but still fun for tourists. This study aims to find out about how much influence the Brand Positioning Fun, Art and Education against the decision of visiting tourists in Bale Seni Barli-Kota Baru Parahyangan. In this study, the independent variable (X) is the Brand Positioning and the dependent variable was the decision to visit, with a sample of 100 respondents, data collection techniques using a questionnaire (questionnaire), interviews, documentary studies and literature studies, while data analysis techniques using simple regression. The results showed that the influence strategy Brand Positioning Fun, Art and Education on the decision been run Bale Seni Barli-Kota Baru Parahyangan have a strong influence, which amounted to 83%. This shows that when Brand Positioning Fun, Art and Education implemented properly, then the decision to tourists visiting Bale Seni Barli-Kota Baru Parahyangan will increase. Keywords: positioning, visit decision, bale seni barli